Centering Equity in Sustainable Food Systems Education - Sterling, Eleanor J.; Betley, Erin; Ahmed, Selena; Akabas, Sharon; Clegg, Daniel J.; Downs, Shauna; Izumi, Betty; Koch, Pamela; Kross, Sara M.; Spiller, Karen; Teron, Lemir; Valley, Will (Frontiers in Sustainable Food Systems, 2021)
Sustainable food systems education (SFSE) is rapidly advancing to meet the need for developing future professionals who are capable of effective decision-making regarding agriculture, food, nutrition, consumption, and waste in a complex world. Equity, particularly racial equity and its intersectional links with other inequities, should play a central role in efforts to advance SFSE given the harmful social and environmental externalities of food systems and ongoing oppression and systemic inequities such as lack of food access faced by racialized and/or marginalized populations. However, few institutional and intra-disciplinary resources exist on how to engage students in discussion about equity and related topics in SFSE. We present perspectives based on our multi-institutional collaborations to develop and apply pedagogical materials that center equity while building students' skills in systems thinking, critical reflection, and affective engagement. Examples are provided of how to develop undergraduate and graduate sustainable food systems curricula that embrace complexity and recognize the affective layers, or underlying experiences of feelings and emotions, when engaging with topics of equity, justice, oppression, and privilege.